Editorial - Escobar, John Willmer (Cuadernos de Administración, 2021)
The high increases in freight transportation costs worldwide have generated a container crisis, impacting the global supply chains due to fast-increasing product prices. This situation could raise the global international inflation rate, provoking the devaluation of different currencies against the dollar. The increased cost of maritime transport will affect some products, impacting their added value. For instance, some furniture, textile, handcraft, artisanal candles, clothing, and leather products could lose their competitive advantage for their emerging producer economies. Due to the Covid-19 pandemic, maritime freight rates are expected to remain high for at least one year, affecting economic trade and demand worldwide and causing a shortage of several products. Such a situation is a critical effect of the lockdowns that slowed down industrial activity. The vertiginous increase in freight transportation rates is due to a multiplicity of factors, the vast majority of them having to do with the pandemic, and it is not yet clear how long this crisis could last. This ongoing crisis is known as the "container crisis" and entails an unusual shortage of available space to transport products from Asia to the rest of the world. Besides the lack of containers and high shipping costs, there have been port jams and temporary shutdowns in some terminals due to strict measures to control the new covid-19 strains. We hope that the massive vaccine rollout worldwide could improve the maritime transportation flow, which moves 99% of the total load (in tons) worldwide. The Colombian industry has suffered a shortage of raw materials, over-production costs, and long delays in lead times, forcing some small- and medium-sized companies to shut down due to inputs being unavailable for their average production. Editorial Note The Journal Cuadernos de Administración needs to thank Prof. Carlos Hernan Gonzales for his invaluable years’ long work as an editor that allowed the Journal significant achievements. Among the most significant achievements is the Journal being categorized in the Emerging Sources Citation Index (ESCI). We hope that Prof. Carlos Hernan will continue supporting the Journal through his participation in the editorial board team. The Journal brings new, significant changes seeking to increase its visibility and ranking: Calls for papers for each volume will be relinquished, and a permanent call for papers will be in place. The Journal will have a "Forthcoming Papers" section, papers that will have been peer-reviewed and accepted for publication but are not yet published because final changes are pending and still need to be assigned a volume or issue. The order they are published does not indicate the order of their final assignment to a volume. These papers can be cited as forthcoming papers. According to the following link, papers must meet a minimum level of English above the 75th percentile https://secure.aje.com/en/researcher/grammar-check. This 71st issue of the Journal Cuadernos de Administración corresponds to the September-December 2021 period. The eight papers published in issue 71 come from the previous call, whose authors submitted their manuscripts to our editorial process from several countries and different regions of Colombia. The Journal thanks our reviewers, who supported us through their experience and expertise in assessing each paper. The eight research papers published attest to the high quality of several aspects in business, marketing, finance, and social responsibility, among other areas. The first paper, called "Visual neuromarketing strategies in two shopping malls in the city of Cúcuta, Colombia," seeks to describe the visual neuromarketing practices present in two shopping malls in the city of Cúcuta (Colombia). A quantitative study with a descriptive, non-experimental, cross-sectional design using an observation guide and a questionnaire is implemented. The second paper, called "Case Analysis: Financial viability for the commercialization of physicochemical testing services at the Antioquia Liquor and Alcohol Factory (ALAF)," studies market profitability for physicochemical testing of alcoholic beverages according to the transformation in its legal nature. The proposed approach includes the costing of tests by using accounting and the analytical procedures used by the laboratory. The paper "A framework explaining the entrepreneurial intentions of engineering students in public universities" seeks to explain the Entrepreneurial Intent (EI) of university students enrolled in engineering programs at the public university of the state of Guanajuato (Mexico). The proposed approach combines the Theory of Planned Behavior, formal and informal institutional factors, and two individual traits. The fourth paper, "Corporate Governance and Organizational Social Responsibility: discussion about the Multilatinas case," explores the relationship between Corporate Governance and Corporate Social Responsibility. This relationship is analyzed considering the interest of the majority-owners-block-family and CEO about the firm outlays for the Organizational Social Responsibility. The paper "Announcements Effect of Corporate Bond Issuance on Stock Returns: Evidence from Chile" measures the effect of announcing a corporate bond issuance on stock returns for companies listed on the Santiago de Chile Stock Exchange (BCS). An event study measures the effect of announcing a corporate bond issuance on stock return, and this methodology calculates abnormal returns for the days of the event. In the work "Internationalization and open innovation in SMEs from the horticultural sector in Colombia," the authors empirically assess the relationship between open innovation, exploration, and exploitation activities in the context of internationalization of horticultural-sector SMEs’ from Northern Valle del Cauca, Colombia. The study is based on a sample of 102 SMEs and the determination of a partial least squares structural equation model (PLS-SEM) to test a series of research hypotheses. The last research paper, "Sustainable segmentation for ecological personal hygiene products in the hard discount format," considers the issue of sustainable consumption of personal hygiene products in countries like Colombia. A quantitative approach with a descriptive correlational scope was employed to analyze the relationship between consumers’ environmental practices and their intention of purchasing personal hygiene products. Finally, the last paper, a reflection paper called "Bank financing management with a value chain approach in Cuba," tackles the value chain concepts and the value chain approach from productive articulation. The methodology used in this work includes the analysis, synthesis, and deduction of the theoretical-methodological aspects of bank financing management. The Universidad del Valle’s Faculty of Administration’s 71st issue of Cuadernos de Administración consolidates us as a prestigious Journal for disseminating scientific knowledge in several areas. The Journal wishes to thank the authors of each of these eight papers and the peer reviewers who supported our editorial process, always bearing in mind that each article’s content is its authors’ responsibility.